Comparison on Different Data Mining Algorithms - Chamatkar, Aruna J; Butey, PK (International Journal of Computer Sciences and Engineering, 2014)
Data mining an interdisciplinary research area spanning several disciplines such as machine learning, database system, expert system, intelligent information systems and statistic. Data mining has evolved into an active and important area of research because of previously unknown and interesting knowledge from very large real-world database. Many aspects of data mining have been investigated in several related fields. A unique but important aspect of the problem lies in the significance of needs to extend their studies to include the nature of the contents of the real world database. In this paper we are going to compare the three different algorithms which are commonly used in data mining. These three algorithms are CHARM Algorithm, Top K Rules mining and CM SPAM Algorithm.